Biodiversidade de bactérias endofíticas em malpighia emarginata e avaliação de isolados com potencial biotecnológico - Specian, Vânia (2014)
The Malpighia emarginata, popularly known as "acerola", was introduced in Brazil in the 1950s. It is a shrub that grows in areas with tropical and subtropical climate, known for its resistance and rusticity, besides being very attractive due to the vitamin C found in its fruit, which can be consumed in natura or as juices and jellies. The endophytic microorganisms have been isolated from all plant species studied and have biotechnological potential for the control of pathogens, growth promotion, production of secondary metabolites and several enzymes. Endophytic bacteria live in symbiosis with the plant and move between stages of epiphytic and endophytic colonization, and thus can provide ecological benefits to the plant or even have a neutral effect. To ensure the efficiency of the biological control is necessary to know the ecology of the pathogen and the antagonist. Endophytic bacteria have a high potential to control pathogens, due to their competition for space and nutrients in the interior of the plant. The endophytes have high capacity for the production of several enzymes with numerous properties and biotechnological applications, and also can be used in other interesting areas, as phosphate solubilization. The sequencing of 16S rDNA gene, combined with PCR technique, became a universal standard for bacterial identification and classification, being used to study the diversity of endophytic bacteria. Therefore, the objectives of this work were to study the diversity of endophytic bacteria present in M. emarginata and analyze their biotechnological potential for the solubilization of inorganic phosphate, the biological control of plant pathogens and the in vitro production of extracellular enzymes. It was possible to identify 36.94% of the isolates by sequencing of 16S, distributed in the following genera: Acinetobacter, Aureimonas, Bacillus, Cellulomonas, Enterobacter, Microbacterium, Micrococcus, Pseudomonas and Staphylococcus; more than 30% were identified to the species level. Regarding the evaluation of the phosphate solubilization, 17.64% of bacteria were positive. Many isolates were also able to inhibit up to 89.09% the pathogens growth The halos produced in the enzyme activity reached up to 4.80. This study demonstrated the existence of genetic diversity in the endophytic community of M. emarginata and the biotechnological potential of some isolates for the phosphate solubilization, biological control and the production of enzymes of commercial interest.